Deep Foundation Element Supported Mat Design And Construction In An Urban Setting - Satyajit A. Vaidya (Deep Foundations Institute, 2010)
This paper presents a case-study in the design and construction of deep foundation element supported mats for two residential towers on an18,000-square-foot site in Brooklyn, New York. Based on site sub-surface conditions, conventional mat foundations bearing on medium dense sand, having an allowable bearing capacity of 3 tsf, were originally anticipated for the 16 and 25-story towers. However, when the tower shear walls were relocated to the edges of the mat foundations due to architectural revisions, the significantly increased mat edge contact stresses applied to the soil subgrade resulted in calculated settlements of a magnitude that would adversely impact the proposed structures and the neighboring/bordering lot-line building and rail transit subway structures. To address this issue, deep foundation element supported mats were designed for the towers. The design was performed as an iterative process involving structural SAFE and geotechnical Plaxis finite element computer analysis to develop a coordinated geo-structural model of the foundation system. Initial presumptive design values of 45 pci and 445 kips/inch were used for the modulus of subgrade reaction and minimum deep foundation element stiffness, respectively. The designed foundation system consisted of 40 and 60-inch-thick mat foundations for the 16 and 25 story towers, respectively. Initially, the deep foundation elements were designed as 50-foot-long, 14-inch-diameter elements installed to sustain a maximum individual compressive load of 250 tons. The final deep foundation element design was subsequently refined to consist of a 48-foot-long, drilled and grouted IBO Titan 103/51 element designed to sustain a maximum load of 167 tons. Subsequent field load tests on the deep foundation elements confirmed element stiffness ranging from 1,040 to 1,530 kips/inch, with measured mobilized side shear of about 29 psi. The mat foundation reinforcement was adjusted for the pile stiffness values determined in the field load tests, and the deep foundation supported mats were constructed. The two towers were subsequently constructed, and have performed successfully.